2020
DOI: 10.2147/ijn.s265061
|View full text |Cite
|
Sign up to set email alerts
|

<p>AT101-Loaded Cubosomes as an Alternative for Improved Glioblastoma Therapy</p>

Abstract: Introduction: AT101, the R-(-)-enantiomer of the cottonseed-derived polyphenol gossypol, is a promising drug in glioblastoma multiforme (GBM) therapy due to its ability to trigger autophagic cell death but also to facilitate apoptosis in tumor cells. It does have some limitations such as poor solubility in water-based media and consequent low bioavailability, which affect its response rate during treatment. To overcome this drawback and to improve the anti-cancer potential of AT101, the use of cubosome-based f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 66 publications
1
45
0
2
Order By: Relevance
“…Thus, an urgent need exists to develop alternative, more effective treatment strategies. In addition to the preferred chemotherapeutic drug TMZ, a promising candidate for the treatment of GBMs is AT101 [ 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. AT101 is able to trigger autophagic, mitophagic, or apoptotic cell death by versatile mechanisms of action as the inhibition of Bcl-2 proteins, the induction of mitochondrial dysfunction, or by modulating serval signaling pathways in a specific manner [ 22 , 23 , 24 , 25 , 26 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Thus, an urgent need exists to develop alternative, more effective treatment strategies. In addition to the preferred chemotherapeutic drug TMZ, a promising candidate for the treatment of GBMs is AT101 [ 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. AT101 is able to trigger autophagic, mitophagic, or apoptotic cell death by versatile mechanisms of action as the inhibition of Bcl-2 proteins, the induction of mitochondrial dysfunction, or by modulating serval signaling pathways in a specific manner [ 22 , 23 , 24 , 25 , 26 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Here, in our opinion, a local application of AT101 directly in the tumor resection cavity (e.g., by nanoparticles or (biodegradable) drug carrier devices) together with systemic treatment with TMZ will be the most promising approach. Using this local treatment strategy of AT101, it is possible to overcome the known relatively low bioavailability of AT101 after systemic treatment [ 20 ], and to analyze the potential of AT101 to eradicate TMZ-resistant glioblastoma cells, which in most cases are characterized by pronounced stem-like cell characteristics [ 17 ]. Further, since it was shown that AT101 was a competent enhancer of radiation-induced apoptosis in head and neck squamous cell carcinoma in vitro [ 56 ], a combination of AT101 and radiation might also be feasible to treat glioblastomas more efficiently.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations